「社団法人 糖業協会所蔵 植民地期台湾産業・経済関係史料 マイクロ版集成」より - (:unkn) unknown (丸善株式会社, 1999)
Guide to the microfilm set, Shadan hōjin Tōgyō Kyōkai shozō Shokuminchiki Taiwan sangyō, keizai kankei shiryō maikuro-ban shūsei. The set includes part one, with 34 microfilm reels, and part two, with 17 reels. The guide is organized by topic, with a table of contents at the front. Each section of the guide contains descriptions of content with section, reel, and slide numbers for each item.
Digitized material from the guide to "Shadan hōjin Tōgyō Kyōkai shozō Shokuminchiki Taiwan sangyō, keizai kankei shiryō maikuro-ban shūsei"
Keywords: Industries -- Taiwan -- History -- Sources; Taiwan -- Economic conditions -- To 1945 -- Sources; Taiwan -- History -- 1895-1945; Economic history; Industries; Taiwan